Climate action in MNEs : insights and recommendations from previous research - Pirttijärvi, Heta (Springer Nature, 2026)
Addressing the Sustainable Development Goal of Climate Action is no longer a nice-to-have in the global business environment of multinational enterprises today, as MNEs are facing considerable pressure from various stakeholders while impacting the climate in a tremendous way. However, clear consensus of climate action in MNEs has been lacking, albeit extremely important due to the rising impact and expectations. The article encompasses a systematic literature review to analyze and present what the current literature says about climate action in MNEs. The study finds that although certain elements of climate action are universal to all companies, MNEs need to take additional action on especially collaborative action to ensure success. Additionally, as much of the insights are still highly reactive, future research should focus on concrete proactive actions, such as technology adoption, to fight climate change.